Tanggung Jawab Hukum atas Kejahatan Siber yang Melibatkan Teknologi Artificial Intelligence di Indonesia - Haris Habibi; Suci Ramadani; Rahmayanti Rahmayanti; Khairuddin Siregar; Jhoni Muda Pratama Barus (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The rapid advancement of Artificial Intelligence (AI) technology has fundamentally transformed the landscape of cybercrime in Indonesia by giving rise to various forms of digital offenses that have not been adequately accommodated within the existing legal framework. This study aims to examine the legal regulation of AI-based cybercrime in Indonesia and the legal liability framework applicable to developers, operators, and users when AI systems are utilized to commit criminal acts. This study employs a normative legal research method using statutory, conceptual, and case approaches through the analysis of primary legal materials, including the Law on Electronic Information and Transactions and its amendments, as well as Law No. 27 of 2022 on Personal Data Protection. The findings reveal a significant normative gap, as Indonesia's cybercrime legislation has not been designed to accommodate the autonomous behavior of AI systems. This study concludes that Indonesia requires a dedicated AI governance framework that explicitly regulates the distribution of criminal and civil liability across the AI value chain in order to ensure legal certainty in addressing AI-based cybercrime